Testing the Accuracy of a New and Simpler-Algorithm for Determining the Time of Sunrise, Midday, and Sunset - M.T. Saidah Sakinah; H.B. Nor'ain (Universiti Sains Islam Malaysia, 2024)
The time of sunrise, midday and sunset is determined according to the movement of the sun. There are many applications can be obtained once the time of sunrise, midday and sunset are known. By the sun, the Muslims calculate the times for daily prayer. It is required to determine the exact time for every times prayer. So that, this research was done to testing the accuracy of the new and simpler algorithm for determining the time of sunrise, midday and sunset.The testing was including the differentiation of value taken from the simpler algorithm in Excel and compare it with the values obtained from the system provided by website of NASA.After comparing the both data, then the results can be obtained by converted it into graph of time versus day for one year to be analysis.